The impact of group design projects in engineering on achievement goal orientations and academic outcomes. Issue 10 (26th November 2017) - Rambo-Hernandez, Karen E.; Atadero, Rebecca A.; Balgopal, Meena
Abstract: This study examined the impact of incorporating group design projects into a second-year engineering class on achievement goal orientations and two academic outcomes: concept inventory and final exam scores. In this study, two sections were taught using lecture format, but one section also completed three group design projects as part of their curriculum. The intervention of incorporating group design projects had a positive effect on mastery goals and a negative effect on performance-approach goals. The effect of the intervention on academic outcomes was mediated by mastery goals but not performance-approach or performance-avoidance goals. Implications and future directions are discussed.